The Utility of Speech-Language Biomarkers to Predict Oral Feeding Outcomes in the Premature Newborn - Bartolome, Ruby (Am J Speech Lang Pathol, 2020)
PURPOSE: Successful oral feeding and speech emergence are dependent upon the coordination of shared oral muscles and facial nerves. We aimed to determine if the speech-associated genes, forkhead box P2 (FOXP2), contactin-associated protein-like 2 (CNTNAP2), glutamate receptor, ionotropic, N-methyl D-aspartate 2A (GRIN2A), and neurexin 1, were detectable in neonatal saliva and could predict feeding outcomes in premature newborns. METHOD: In this prospective, observational, preliminary study, saliva collected from 51 premature infants (gestational ages: 30–34 6/7 weeks) at different stages of oral feeding development underwent gene expression analysis. Binary (+/–) expression profiles were explored and examined in relation to days to achieve full oral feeds. RESULTS: GRIN2A and neurexin 1 rarely amplified in neonatal saliva and were not informative. Infants who amplified FOXP2 but not CNTNAP2 at the start of oral feeds achieved oral feeding success 3.20 (95% CI [−2.5, 8.9]) days sooner than other gene combinations. CONCLUSIONS: FOXP2 and CNTNAP2 may be informative in predicting oral feeding outcomes in newborns. Salivary analysis at the start of oral feeding trials may inform feeding outcomes in this population and warrants further investigation.